Vaterite growth and dissolution in aqueous solution III. Kinetics of transformation - Kralj, Damir; Brečević, Ljerka; Kontrec, Jasminka (Journal of crystal growth, 1997)
The kinetics of transformation of vaterite to calcite in aqueous solution was studied at temperatures between 25°C and 45°C and ionic strengths between 15 and 415 mmol dm −3. Both vaterite and calcite precipitated spontaneously, with vaterite being initially the only solid phase in the system. The progress of the transformation was followed by recording pH as a function of time. It was found that this transformation was solution-mediated, and that the growth of calcite was the rate-determining process. This conclusion was additionally supported by a mathematical model made to predict changes of both the solid phase and the solution during the overall process. The model is based on the rate constants and the mechanism of the processes involved in the transformation, as well as on the experimentally determined number density of the crystals formed. The seeded growth kinetics of calcite was determined in separate experiments, at temperatures between 10°C and 55°C, and the rate law was found to be parabolic. The high activation energy obtained for the temperature dependent rate constants E a = 55.29 kJ mol −1, supports the assumption that the calcite growth was controlled by processes at the crystal surface.